Burston, Jack - (:unkn) unknown (My University, 2026)
Jack Burston holds the position of Honorary Research Fellow in the Language Centre of the Cyprus University of Technology. He is a language-teaching specialist with a formal background in theoretical and applied linguistics, second language acquisition and testing. He also has considerable expertise in computer-assisted language learning, foreign language software evaluation, language centre design and professional faculty development. His current research is focused on Mobile-Assisted Language Learning. Jack has been a member of the Editorial Board of the CALICO Journal since 1995, served as Software Review Editor of the CALICO Journal for 13 years and is a former member and chair of the CALICO Executive Board. He was the Editor of the IALLT Language Center Design Kit and the Digital Language Lab Solutions volume.
Keywords: social